Professor Wellstone goes to Washington : the inside story of a grassroots U.S. Senate campaign - McGrath, Dennis J. (University of Minnesota Press, 1995)
How did a fortysomething college professor and outspoken liberal activist manage to unseat from the Senate one of the nation's most skillful politicians and money raisers? This engaging insiders' account of Paul Wellstone's successful grassroots Senate campaign explains it all for you. Written by two political reporters for the Minneapolis Star Tribune who covered the Wellstone campaign from its inception, Professor Wellstone Goes to Washington provides a revealing and evocative behind-the-scenes look at a memorable chapter in U.S. Senate campaign history.